INDIVIDUAIZATION IN TEACHING ENGLISH IN THE MIDDLE LEVEL. - qizi, Akhmadjonova Shakhnoza Makhamadjon; Makhamadovna, Zakirova Mukhlisakhon (The journal of contemporary issues in business and government, 2021)
Modern training, including foreign languages, is investigated in this article, focused on a medium-sized student. Based on many studies and personal observations, it can be said that schooling does not pay due attention to the individual characteristics of students, which is why weak students become unsuitable, and strong lose interest in the subject. That is why the issue of individualized learning becomes relevant, especially in teaching foreign languages due to group form of training.